Islamic Legal Review of the Tradition of Laylat al-Henna in Wedding Ceremonies in Arab-Indonesia Descendant Families in Palu City - Hamsah, Yudi; Rahmy, Irma Nur; Al-Habsyi, Fathiya (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2024)
Abstract: One tradition that is currently still in effect and practiced by the community is the tradition of using henna in wedding ceremonies. The issue that arises in this henna usage tradition is that, with the advancement of technology, various types of henna have proliferated in the market, some of which are mixed with chemicals that can form a waterproof layer, thus making the color of the henna more intense and accelerating absorption. The diversity of henna types has led many people to doubt the naturalness of the ingredients contained in henna paste and may impede purity in worship. The purpose of this research is to analyze the issues related to the use of henna in the context of Islamic law, using empirical legal research methods and a sociology of Islamic law approach. This research then produces several conclusions: first, there are two types in the categorization of henna paste, namely natural henna with a reddish-brown color and black henna, which is the result of mixing natural henna with chemical substances. In the community's view, black henna should not be used. Second, the tradition of using henna in the Arab-Indonesian community in Palu is referred to as Laylat al-Henna, which has symbolic meaning, such as the hope that the prospective bride will soon have offspring, bringing happiness to the family that will be established. The Laylat al-Henna tradition falls into the category of 'urf shahih because it does not contradict Sharia, both in the text and other legal sources.Abstrak: Penggunaan henna dalam upacara pernikahan masih menjadi tradisi yang umum di masyarakat. Masalah yang muncul dalam tradisi penggunaan henna ini adalah, dengan kemajuan teknologi, berbagai jenis henna telah banyak beredar di pasaran, beberapa di antaranya dicampur dengan bahan kimia yang dapat membentuk lapisan tahan air sehingga membuat warna henna lebih pekat dan mempercepat penyerapan. Keberagaman jenis henna ini membuat banyak orang meragukan kealamian bahan yang terkandung dalam pasta henna dan dapat menghambat kesucian dalam beribadah. Tujuan dari penelitian ini adalah untuk menganalisis permasalahan terkait penggunaan henna dalam konteks hukum Islam, dengan menggunakan metode penelitian hukum empiris dan pendekatan sosiologi hukum Islam. Penelitian ini menghasilkan beberapa kesimpulan: pertama, terdapat dua jenis dalam klasifikasi pasta henna, yaitu henna alami dengan warna merah kecoklatan dan henna hitam yang merupakan hasil campuran henna alami dengan bahan kimia. Dalam pandangan masyarakat, henna hitam sebaiknya tidak digunakan. Kedua, tradisi penggunaan henna di kalangan masyarakat Arab-Indonesia di Palu disebut dengan Laylat al-Henna, yang memiliki makna simbolis, seperti harapan agar calon pengantin segera mendapatkan keturunan, membawa kebahagiaan bagi keluarga yang akan dibentuk. Tradisi Laylat al-Henna termasuk dalam kategori 'urf shahih karena tidak bertentangan dengan syariat, baik dalam teks maupun sumber hukum lainnya.